Dynamical resonant charge transfer of fast C−, O−, F− ions and water covered Si(111) surface. (March 2017) - Xiong, Feifei; Gao, Lei; Liu, Yuefeng; Lu, Jianjie; Liu, Pinyang; Qiu, Shunli; Qiu, Xiyu; Guo, Yanling; Chen, Ximeng; Chen, Lin
Abstract: The experiment of 6.5–22.5 keV C −, O − and F − ions scattering on water covered Si(111) surface has been performed. It is found that the positive-ion fraction is very low and increases monotonically as a function of perpendicular exit velocity and exit angle. In particular, the negative-ion fraction increases monotonically with perpendicular exit velocity for specular scattering, and for a given incident energy the angle dependence of the fraction is nonmonotonic. We interpret the observed positive ions in terms of inelastic binary collision, and adopt a modified resonant charge transfer model to calculate the bell-shaped negative-ion fraction. We find that the neutral yield at short ion-surface distance is nonzero and obeys well an exponential dependence. It strongly indicates that a dynamical equilibrium for negative ion formation is never achieved at short distances, and the band gap effect on charge transfer can be neglected to a large extent in this relatively high energy region. Highlights: Positive and negative ion fractions are measured as a function of perpendicular exit velocity and exit angle. A modified charge transfer model has been used to calculate negative ion fractions. The comparison to previous work has been discussed.